Coronavirus outbreaks including COVID-19 and impacts on medical education: a systematic review - Kelly Kelly; Lie Rebecca Yen Hwei; Gilbert Sterling Octavius (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Since the beginning of 2020, the world has been affected by the novel coronavirus COVID-19 pandemic. The virus’ infectious nature pushed all sectors to implement social distancing measures in an effort to limit its transmission, including the education sector. We searched PubMed and Science Direct on June 12th and found 24 papers that are relevant to our review. After the World Health Organization announced that COVID-19 is a global threat, various countries took a variety of measures to limit the disease spread such as social distancing, self-quarantine, and closing public facilities that hold large gatherings, including universities and schools. Hospitals started to prioritize services for COVID-19 cases. Medical education programs are also affected by this disease, but not continuing in-person classes outweighs any benefit from traditional teaching methods. The previous Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) pandemics have shown ways to shift medical education to online platforms. In the current pandemic, online meetings are being used to hold lectures, classes, laboratory practices, and clinical skills classes. For clerkship students, online platforms might not be feasible because this eliminates patient-doctor relationships, but it appears for now to be the only option. Some institutions have involved medical students in the frontlines altogether. We encourage all parties to constantly evaluate, review, and improve the efforts of continuing medical education, especially during this pandemic. Further research is needed to evaluate students’ performance after adopting e-learning and to discover the best methods in medical education in general and clerkship education in particular.